2017
DOI: 10.1021/acsnano.7b01442
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Delivery To Accelerate Incisional Wound Healing Following Single Irradiation of Near-Infrared Lamp on the Coordinated Colloids

Abstract: Traditional wound care methods include wound infection control, adequate nutritional supplements, education of changing position every 2-3 h to avoid tissue hypoxia, vacuum assistant closure, debridement, skin graft, and tissue flap. Electric current stimulation, ultrasound, laser, and hydrotherapy have emerged as adjuvant therapies. However, most, if not all, of these therapies are expensive, and the treatment results are variable. The development of the active methods to improve wound healing is mandatory. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…The NIR light with 700–1000 nm wavelength has been used in clinical treatment for promoting wound healing and many previous studies showed that the NIR light can accelerate wound healing through inflammation inhibition, angiogenesis enhancement, and collagen deposition . Here, we aim to demonstrate whether the ISASE equipped with NIR LEDs could accelerate skin wound healing of rats.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The NIR light with 700–1000 nm wavelength has been used in clinical treatment for promoting wound healing and many previous studies showed that the NIR light can accelerate wound healing through inflammation inhibition, angiogenesis enhancement, and collagen deposition . Here, we aim to demonstrate whether the ISASE equipped with NIR LEDs could accelerate skin wound healing of rats.…”
Section: Resultsmentioning
confidence: 97%
“…In the course of irradiation, the treated rats showed less weeping and suppurating, indicating the inhibited inflammatory response over the wound bed. To identify the putative appearance, hematoxylin and eosin (H&E) stain was performed to measure the inflammation cells in skin tissue over wounds . On day 3, the regenerated tissue was abnormal, with much more granulation tissue, in the nonirradiated control group (Figure d‐i) compared with the irradiated rat (Figure d‐ii).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The promising physical, mechanical, and in vitro biological properties of the bilayer scaffold 21 encouraged us to perform the present study and investigate the niche response in murine skin wound model. There are different types of animal wound models, including incisional, 30 excisional, 31 burn, 32 and GT models. 33 Among which, the excisional wound model allows for the broadest assessment of wound healing mechanisms because the healing initiates from the wound margins.…”
Section: Discussionmentioning
confidence: 99%
“…Carbonate‐enriched hot water has been demonstrated to significantly improve wound closure; however, the influence of the other ions potentially beneficial to the healing (e.g.,: calcium) was not studied. Local delivery of carbon dioxide releasing microparticles has been shown to improve blood flow, wound closure, as well as microvessel formation and collagen deposition …”
Section: Carbon Dioxide Bicarbonates and Carbonatesmentioning
confidence: 99%